(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This study examines the mechanisms for stimulating investment activity in districts and their role in promoting regional economic development. The research highlights the importance of creating favorable institutional, financial, and infrastructural conditions to attract both domestic and foreign investments at the district level. Particular attention is given to improving the investment climate, strengthening local governance mechanisms, providing tax and financial incentives, and developing modern infrastructure.